Immunohistochemical and ultrastructural study of the immune cell system and epithelial surfaces of the respiratory organs in the bimodally breathing African sharptooth catfish (Clarias gariepinus Burchell, 1822). Issue 11 (23rd February 2022) - Maina, John Ndegwa; Icardo, Jose Manuel; Zaccone, Giacomo; Aragona, Marialuisa; Lauriano, Eugenia Rita; Alesci, Alessio; Albano, Marco; Guerrera, Maria Cristina; Germana, Antonino; Fernandes, Jorge Manuel Oliveira; Kiron, Viswanath; Capillo, Gioele
Abstract: Acetylcholine (Ach) represents the old neurotransmitter in central and peripheral nervous system. Its muscarinic and nicotinic receptors (mAChRs and nAChRs) constitute an independent cholinergic system that is found in immune cells and play a key role in the regulation of the immune function and cytokine production. Gas exchanging surfaces of the gills and air‐breathing organs (ABOs) of the sharptooth catfish Clarias gariepinus were investigated using ultrastructural and confocal immunofluorescence techniques. This study was predominantly focused on the structure of the immune cell types, the expression of their neurotransmitters, including the antimicrobial peptide piscidin 1, and the functional significance of respiratory gas exchange epithelia. A network of immune cells (monocytes, eosinophils, and mast cells) was observed in the gill and the ABO epithelia. Eosinophils containing 5‐hydroxytryptamine (5‐HT) immunoreactivity were seen in close association with mast cells expressing acetylcholine (Ach), 5‐HT, neuronal nitric oxide synthase, and piscidin 1. A rich and dense cholinergic innervation dispersing across the islet capillaries of the gas exchange barrier and the localization of Ach in the squamous pavement cells covering the capillaries were evidenced byVAChT antibodies. We report for the first time that piscidin 1 (Pis 1)‐positive mast cells interact with Pis 1‐positive nerves found in the epithelia of the respiratory organs. Pis 1 immunoreactivity was also observed in the covering respiratory epithelium of the ABOs and associated with a role in local mucosal immune defense. The above results anticipate future studies on the neuro‐immune interactions at mucosal barrier surfaces, like the gill and the skin of fish, areas densely populated by different immune cells and sensory nerves that constantly sense and adapt to tissue‐specific environmental challenges.